KEMAMPUAN ANAK DALAM MENGKOMUNIKASIKAN MASALAH - Tanjung, Salsabila Hasiana (UNIVED Press, Universitas Dehasen Bengkulu, 2022)
The ability of children to express an opinion is an ability of communication skills that are important for children to have. This research was carried out with the aim of examining the implementation of learning by using media images that show problems around children, such as pictures of scattered garbage and pictures of flooded areas in order to stimulate children's ability to communicate ideas of children's thoughts. The implementation of the research was tested on 35 children by involving 2 teachers. The research was carried out by observing the behavior that emerged. The use of pictures using material that is easy for children to recognize will make it easier for children to express their ideas.